Day-Ahead Dynamic Economic Emission Dispatch Considering Photovoltaic Predicted Output Using Sailfish Optimizer and Simulated Annealing - Wisbar, Andi Hidayah; Priyadi, Ardyono; Lystianingrum, Vita (Department of Electrical Engineering ITS and FORTEI, 2024)
The Indonesian government continues to focuson boosting equitable access to environmentally friendlyelectricity to all levels of Indonesian society. This can be shownthrough the achievement of an electrification ratio of 99.40 percent in the third quarter of 2021 coupled with promisinggrowth in the capacity of Renewable Energy (RE) powerplants. Economic Dispatch (ED) aims to optimize the outputpower of generating units to minimize the total cost of powersystem operations. With the application of ED, the minimumgeneration cost will be obtained for the production of electricpower generated by generating units in an electricity systemwhile still paying attention to constraints. For hybrid plantssuch as the Selayar Solar Power Plant, the challenge toperforming ED is the intermittency of solar energy. So thatbefore the ED is carried out, solar radiation forecasting iscarried out using LSTM. To measure the accuracy offorecasting, RMSE, MSE MAE, and MAPE are used withaverage results of 6.311, 40.11, 4.61, and 4.87. With theapplication of ED, the minimum generation cost is obtained forthe production of electric power generated while stillconsidering the constraints. Through ED, fuel allocation can beoptimized, helping to reduce production costs and carbonemissions, and making a positive contribution toenvironmental sustainability. To improve ED results in thesailfish optimizer, the use of simulated annealing is added sothat the results have lower total cost and emission values thanED without simulated annealing. Rp 128.024 and 398 kg,respectively.